2008
DOI: 10.1016/j.stem.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Wnt, Activin, and BMP Signaling Regulate Distinct Stages in the Developmental Pathway from Embryonic Stem Cells to Blood

Abstract: The embryonic stem cell differentiation system was used to define the roles of the Activin/Nodal, BMP, and canonical Wnt signaling pathways at three distinct developmental stages during hematopoietic ontogeny: induction of a primitive streak-like population, formation of Flk1(+) mesoderm, and induction of hematopoietic progenitors. Activin/Nodal and Wnt, but not BMP, signaling are required for the induction of the primitive streak. Although BMP is not required for primitive streak induction, it displays a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
273
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(315 citation statements)
references
References 49 publications
31
273
5
Order By: Relevance
“…5F). Our data agree with recent evidence obtained from murine ES cell cultures modeling primitive and definitive hematopoietic programs (7). In these studies, β-catenin, BMP, and Activin signaling synergized to regulate the formation of Flk1 + mesoderm, which has hematopoietic potential, and β-catenin signaling was required for specification of the primitive erythroid lineage (7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5F). Our data agree with recent evidence obtained from murine ES cell cultures modeling primitive and definitive hematopoietic programs (7). In these studies, β-catenin, BMP, and Activin signaling synergized to regulate the formation of Flk1 + mesoderm, which has hematopoietic potential, and β-catenin signaling was required for specification of the primitive erythroid lineage (7).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies using in vitro differentiation of ES cells and manipulation of zebrafish embryos point to a role for Wnt signaling in primitive blood development (7,8). However, there is still no direct conclusive evidence for a role for Wnt signaling in the formation of primitive blood in vivo.…”
mentioning
confidence: 99%
“…The establishment of a defined and stepwise strategy for generating hematopoietic cells from embryonic stem cells is valuable for the study of early hematopoietic development, and the EB strategy has been reported in the hematopoietic differentiation of mouse embryonic stem cells (mESCs) [8][9][10]. In these systems, hematopoietic differentiation was generally divided into steps containing BRACHYURY + embryonic primitive streak (PS), KDR + /Flk1 + mesoderm and CD41 + hematopoietic progenitor generation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, BMP4 promotes the differentiation towards mesendodermal lineages and also regulates, either positively or negatively, the further commitment of mesendodermal precursors into their different fates. [5][6][7][8] Gene expression in ESCs is regulated by a complex network of transcription factors. 9,10 In addition, numerous results indicate that miRNAs are crucial regulators of the gene expression programs that drive ESC differentiation.…”
mentioning
confidence: 99%